Preparation method of light rare earth Pr-based ultrahigh magnetostrictive material

By employing a unique composition design and composite additive system, combined with optimized preparation processes, the problems of easy oxidation and insufficient magnetostrictive properties of pure praseodymium-iron-based alloys have been solved, achieving high performance and thermal stability of light rare earth Pr-based ultra-high magnetostrictive materials, thus broadening their application range.

CN121439431AActive Publication Date: 2026-01-30LIAOCHENG GUANXIAN SHANGAO SUPERHARD MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511748357.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-26
Publication Date
2026-01-30
Estimated Expiration
2045-11-26

AI Technical Summary

Technical Problem

In the existing technology, pure praseodymium-iron based alloys are easily oxidized and their magnetostrictive properties are difficult to fully utilize, and it is difficult to synthesize a stable phase structure under normal pressure.

Method used

By employing a unique composition design and composite additive system, combined with an optimized preparation process, additives A and B are introduced. Additive A provides a uniform fine-grained structure and physical barrier, while additive B improves interfacial bonding. Combined with a specific high-pressure hot pressing process, a light rare earth Pr-based ultra-high magnetostrictive material is prepared.

Benefits of technology

This technology enables high-performance output of materials under low driving fields, improves magnetostrictive properties and mechanical strength, broadens the application range, solves the synthesis problem caused by the excessively large radius of praseodymium ions, and enhances thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121439431A_ABST
    Figure CN121439431A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of magnetic functional materials, in particular to a light rare earth Pr-based ultrahigh magnetostrictive material and a preparation method thereof. The light rare earth Pr-based ultrahigh magnetostrictive material comprises the following raw materials in parts by weight: 20-35 parts of praseodymium-neodymium misch metal, 60-75 parts of pure iron, 3-8 parts of metal cobalt, 0.5-2 parts of metal niobium, 0.1-0.5 part of an additive A and 0.5-2 parts of an additive B. The additive A is enriched at a grain boundary; the additive B is used for improving the combination state between the rare earth phase and the ferromagnetic matrix, the directional rotation process of the magnetic domain under the external magnetic field is promoted, and the magnetic field is improved. The effects are combined with the inherent strong magnetocrystalline anisotropy of the Pr element and specific hydrogen decrepitation and magnetic field orientation hot pressing processes, and the magnetostriction strain and driving capacity of the material are synergistically enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of magnetic functional materials, in particular to a light rare earth Pr-based ultrahigh magnetostrictive material and a preparation method thereof. BACKGROUND

[0002] The magnetostrictive material is a functional material with the length synchronously changed with an applied magnetic field, and can be used in medical treatment, military affairs, daily life and the like.

[0003] In the prior art, a pure praseodymium-iron-based alloy has problems of easy oxidation and difficult full play of magnetostrictive performance, and the problems are difficult to be effectively solved through simple composition adjustment or conventional preparation processes, and the ion radius of praseodymium is large, which exceeds the ion proportion for forming a stable phase structure, so that the praseodymium-iron-based alloy is difficult to be synthesized under normal pressure, and based on this, the application provides the preparation method of the light rare earth Pr-based ultrahigh magnetostrictive material. SUMMARY

[0004] The application aims to provide a light rare earth Pr-based ultrahigh magnetostrictive material and a preparation method thereof. The material prepared by the application has ultrahigh magnetostrictive coefficient, excellent mechanical strength and thermal stability, and effectively widens the application range of the material in harsh environments.

[0005] To achieve the above-mentioned purpose, the application provides the following technical scheme. In a first aspect, the light rare earth Pr-based ultrahigh magnetostrictive material comprises the following raw materials in parts by weight: 20-35 parts of praseodymium-neodymium mixed rare earth metal, 60-75 parts of pure iron, 3-8 parts of metal cobalt, 0.5-2 parts of metal niobium, 0.1-0.5 parts of additive A and 0.5-2 parts of additive B. The raw materials of the additive A comprise boron mud, anhydrous magnesium chloride powder and silicon powder. The raw materials of the additive B comprise an additive, a titanate coupling agent and aluminum nitride.

[0006] Further, the additive A is prepared by the following method and the following steps: the anhydrous magnesium chloride powder and the silicon powder are mixed in a mass ratio of (3-5):1, and are placed in a ball mill jar and ball milled at a rotating speed of 300-400 revolutions per minute for 2-4 hours to obtain mixed powder, the boron mud and the mixed powder are mixed in a mass ratio of 1:(1.5-2.5), and are calcined at 650-800 DEG C under argon protection for 2-4 hours, and then are cooled, crushed, sieved through a 200-300 mesh sieve, added with a hydrochloric acid solution with a mass concentration of 5-10%, and reacted at 40-60 DEG C for 1-2 hours, after the reaction, filtered, and the filter residue is washed with deionized water until neutral, and the filtered residue after washing is vacuum dried at 80-100 DEG C to prepare the additive A, wherein the mass of the hydrochloric acid is 5-7 times the mass of the mixed powder.

[0007] Further, the boron mud needs to be pretreated before preparing the additive A.

[0008] Further, the pretreatment of the boron mud comprises the following steps: drying and crushing the boron mud to 60-80 mesh, mixing the crushed boron mud with a reaction solution at a mass ratio of 1:5, adding polyethylene glycol-400, stirring at 200-300 rpm for 20-30 min, standing for 8-10 h, filtering, adding a 5% sodium bicarbonate aqueous solution to the filter residue, reacting for 8-10 min, filtering, drying the filter residue, and crushing it to 80-100 mesh to obtain the pretreated boron mud, wherein the mass of the sodium bicarbonate aqueous solution is 25-30% of the mass of the filter residue.

[0009] Further, the reaction solution is prepared by the following method: mixing succinic acid with deionized water at a mass ratio of 5:(90-95), stirring until the succinic acid is completely dissolved to obtain a succinic acid aqueous solution, and adding potassium dihydrogen phosphate to the succinic acid aqueous solution, stirring at a speed of 100-200 rpm for 10-15 min to obtain the reaction solution, wherein the mass of the potassium dihydrogen phosphate is 3% of the mass of the succinic acid.

[0010] Further, the additive B is prepared by the following method: mixing the additive with a titanate coupling agent at a mass ratio of 1:(0.2-0.4), stirring and reacting at 60-80℃ for 3-7 min, then adding aluminum nitride powder, reacting for 0.5-1 h, cooling, and performing centrifugal separation treatment to obtain a precipitate, washing the precipitate with anhydrous ethanol 2-3 times, and vacuum drying at 70-90℃ to obtain the additive B.

[0011] Further, the additive is prepared by the following method: mixing menthol with gallic acid at a molar ratio of 1:1, stirring at 80-85℃ to obtain a second mixed solution, mixing zinc oxide powder with the second mixed solution at a mass ratio of 1:(4-6), stirring and reacting at 75-80℃ for 3-5 h, adding anhydrous ethanol after the reaction is complete, performing centrifugal separation treatment to obtain a precipitate, washing the precipitate with anhydrous ethanol 2-3 times, and drying to obtain the additive, wherein the volume of the anhydrous ethanol is 1-3 times the volume of the second mixed solution.

[0012] Further, the average particle size of the aluminum nitride powder is less than 100 nm, and the mass of the aluminum nitride is 5-10% of the mass of the additive.

[0013] Further, the mass content of praseodymium in the praseodymium-neodymium mixed rare earth metal is not less than 75%.

[0014] The second aspect is a preparation method of a light rare earth Pr-based ultrahigh magnetostrictive material, comprising the following steps: Step one: put praseodymium-neodymium mixed rare earth metal, pure iron, metal cobalt, metal niobium, additive A and additive B into a vacuum induction melting furnace, vacuumize to 5.0*10-4 Pa, and then vacuumize to 5.0*10-4 Pa 2 Pa above, fill high-purity argon to -0.05 MPa, melt at 1450-1550 DEG C, obtain alloy liquid, pour the alloy liquid into a water-cooled copper mold, and obtain an alloy ingot; Step two: the alloy ingot is subjected to vacuum homogenization annealing, the annealing temperature is 950-1050 DEG C, the annealing time is 10-20 h, and the alloy rod is obtained by wire cutting after cooling; Step three: the alloy rod is placed in a vacuum reactor, hydrogen is absorbed at room temperature, and then dehydrogenation crushing treatment is carried out at 300-500 DEG C, to obtain a crude material, wherein the process parameters of dehydrogenation crushing treatment are set as follows: hydrogen is absorbed at room temperature to 0.1-0.2 MPa, pressure is maintained for 2-4 h, vacuumization is carried out to below 1 Pa, and dehydrogenation is carried out by increasing the temperature to 300-400 DEG C, and the dehydrogenation time is 1-3 h; Step four: the crude material is subjected to orientation pressing forming under a magnetic field with a magnetic field intensity of 1.5-2.5 T, to obtain an intermediate product; Step five: the intermediate product is packaged in pyrophyllite pressure transmission medium, placed in a six-surface hydraulic press, and subjected to heat preservation and pressure at 800-1000 DEG C and a pressure of 4-8 GPa for 10-60 min, and then cooled to room temperature, to obtain a light rare earth Pr-based ultrahigh magnetostrictive material.

[0015] Compared with the prior art, the present application has the following advantages: 1、In the present application, additive A is introduced, which is prepared from boron mud and other raw materials, the boron mud provides abundant magnesium and silicon sources and porous framework, and anhydrous magnesium chloride acts as an activator to promote the reactivity at high temperature, so that additive A is selectively enriched at the grain boundaries during alloy melting and heat treatment, which can inhibit the coarsening trend of the grains at high temperature, and uniform and fine grain structure is obtained, which provides a good micro foundation for the magnetostrictive performance, and the substances enriched at the grain boundaries act as physical barriers to hinder the inward diffusion of oxygen along the grain boundaries, so that the praseodymium element is not easily oxidized at high temperature, and the thermal stability of the material is improved.

[0016] 2. In the present application, by introducing the additive B containing modified additive and aluminum nitride, the additive provides good interface infiltration and bonding sites, and the ultra-fine aluminum nitride particles are dispersed in the phase interface as a hard reinforcing phase, effectively pinning dislocations and refining the magnetic domain structure, both of which improve the interface bonding between the rare earth-rich phase and the ferromagnetic matrix, and promote the effective transmission of stress at the phase interface, reduce the pinning energy of the magnetic domain wall during reorientation, make the magnetic domain more easily oriented under an external magnetic field, thereby inducing a larger magnetostrictive strain under a lower saturation magnetic field, and fully exerting the magnetostrictive properties of the pure praseodymium-iron-based alloy.

[0017] 3. In the present application, the uniform fine-grained structure created by additive A provides a carrier for the interface modification of additive B, which effectively makes up for the deficiency of A in phase interface coupling, improves the magnetostrictive properties and mechanical strength, and realizes high-performance output of the material under low driving field. Combined with a specific high-pressure hot pressing process, the synthesis problem of Pr ion radius being too large to form a stable Laves phase structure under normal pressure is solved. BRIEF DESCRIPTION OF DRAWINGS

[0018] Figure 1 A light rare earth Pr-based ultrahigh magnetostrictive material and its preparation method are proposed. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present application will be described clearly and completely below with reference to the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.

[0020] It should be noted that the raw materials used in the following embodiments are commercially available.

[0021] Embodiment 1: Preparation of the reaction solution: Mix succinic acid and deionized water in a mass ratio of 5:90, stir until the succinic acid is completely dissolved, and obtain a succinic acid aqueous solution. Add potassium dihydrogen phosphate to the succinic acid aqueous solution, stir at a speed of 100 rpm for 10 min, and prepare the reaction solution. The mass of potassium dihydrogen phosphate is 3% of the mass of succinic acid.

[0022] The pretreatment of boron mud: the boron mud is dried and crushed to 60 mesh, the crushed boron mud is mixed with the reaction solution at a mass ratio of 1:5, polyethylene glycol-400 is added, stirring at 200 rpm for 20 min, standing for 8 h, filtering, adding 5% sodium bicarbonate aqueous solution to the filter residue, reacting for 8 min, filtering, drying the filter residue, and crushing to 80 mesh to obtain the pretreated boron mud, wherein the mass of the sodium bicarbonate aqueous solution is 25% of the mass of the filter residue.

[0023] Preparation of additive A: anhydrous magnesium chloride powder is mixed with silicon powder at a mass ratio of 3:1, placed in a ball mill tank, and ball milled at a speed of 300 rpm for 2 h to obtain mixed powder, the pretreated boron mud is mixed with the mixed powder at a mass ratio of 1:1.5, calcined at 650℃ for 2 h under argon protection, cooled, crushed, and sieved through a 200 mesh sieve, 5% hydrochloric acid solution is added, and reacted at 40℃ for 1 h, after the reaction is completed, filtering, washing the filter residue with deionized water until neutral, drying the washed filter residue at 80℃ under vacuum to obtain additive A, wherein the mass of the hydrochloric acid is 5 times the mass of the mixed powder.

[0024] Preparation of additive A: anhydrous magnesium chloride powder is mixed with silicon powder at a mass ratio of 3:1, placed in a ball mill tank, and ball milled at a speed of 300 rpm for 2 h to obtain mixed powder, the pretreated boron mud is mixed with the mixed powder at a mass ratio of 1:1.5, calcined at 650℃ for 2 h under argon protection, cooled, crushed, and sieved through a 200 mesh sieve, 5% hydrochloric acid solution is added, and reacted at 40℃ for 1 h, after the reaction is completed, filtering, washing the filter residue with deionized water until neutral, drying the washed filter residue at 80℃ under vacuum to obtain additive A, wherein the mass of the hydrochloric acid is 5 times the mass of the mixed powder.

[0025] Preparation of additive B: the additive and the titanate coupling agent are mixed at a mass ratio of 1:0.2, stirred at 60℃ for 3 min, then aluminum nitride powder is added, and reacted for 0.5 h, cooled, centrifugally separated to obtain precipitate, washed with anhydrous ethanol for 2 times, and dried at 70℃ under vacuum to obtain additive B.

[0026] The average particle size of the aluminum nitride powder is less than 100 nm, and the mass of the aluminum nitride is 5% of the mass of the additive.

[0027] The mass content of praseodymium in the praseodymium-neodymium mixed rare earth metal is not less than 75%.

[0028] Preparation of light rare earth Pr-based ultrahigh magnetostrictive material:

[0029] Preparation of light rare earth Pr-based ultrahigh magnetostrictive material: Step 1: Place the praseodymium-neodymium mixed rare earth metals, pure iron, metallic cobalt, metallic niobium, additive A, and additive B into a vacuum induction melting furnace, and evacuate to 5.0 × 10⁻⁻⁻⁶. 2 The pressure is above Pa, and high-purity argon gas is introduced to -0.05 MPa. The mixture is then melted at 1450 °C to obtain a liquid alloy. The liquid alloy is then poured into a water-cooled copper mold to obtain an alloy ingot. Step 2: Vacuum homogenization annealing of the alloy ingot is carried out at a temperature of 950℃ for 10 hours. After cooling, the alloy rod is obtained by wire cutting. Step 3: Place the alloy rod in a vacuum reactor and absorb hydrogen at room temperature. Then, dehydrogenate and crush it at 300°C to obtain the coarse material. The process parameters for dehydrogenation and crushing are set as follows: absorb hydrogen at room temperature to a pressure of 0.1 MPa, maintain the pressure for 2 hours, then evacuate to below 1 Pa and heat to 300°C for dehydrogenation for 1 hour. Step 4: The rough material is oriented and pressed into shape under a magnetic field with a strength of 1.5T to obtain the intermediate product; Step 5: The intermediate product is encapsulated in a pyrophyllite pressure-transmitting medium, placed in a six-sided hydraulic press, and kept at 800℃ and 4GPa pressure for 10 minutes. After cooling to room temperature, a light rare earth Pr-based ultra-high magnetostrictive material is obtained.

[0030] Example 2: Preparation of the reaction solution: Succinic acid and deionized water were mixed at a mass ratio of 5:93 and stirred until the succinic acid was completely dissolved to obtain an aqueous solution of succinic acid. Potassium dihydrogen phosphate was added to the aqueous solution of succinic acid, and the mixture was stirred at 200 rpm for 13 min to obtain the reaction solution. The mass of potassium dihydrogen phosphate was 3% of the mass of succinic acid. Pretreatment of boron sludge: After drying the boron sludge, crush it to 80 mesh. Mix the crushed boron sludge with the reaction solution at a mass ratio of 1:5, add polyethylene glycol-400, stir at 250 rpm for 25 min, let stand for 9 h, filter, add 5% sodium bicarbonate aqueous solution to the filter residue, react for 9 min, filter, dry the filter residue, and crush it to 100 mesh to obtain the pretreated boron sludge, wherein the mass of sodium bicarbonate aqueous solution is 27% of the mass of the filter residue.

[0031] Preparation of Additive A: Anhydrous magnesium chloride powder and silicon powder were mixed at a mass ratio of 4:1 and placed in a ball mill jar. The mixture was ball-milled at 400 rpm for 3 hours to obtain a mixed powder. Pretreated boron mud was mixed with the mixed powder at a mass ratio of 1:2 and calcined at 700°C for 3 hours under argon protection. After cooling, the mixture was pulverized and passed through a 300-mesh sieve. A 7% hydrochloric acid solution was added and reacted at 50°C for 1.5 hours. After the reaction was completed, the mixture was filtered. The filter residue was washed with deionized water until neutral. The washed filter residue was vacuum dried at 90°C to obtain Additive A. The mass of the hydrochloric acid was 6 times the mass of the mixed powder.

[0032] Preparation of the additive: Menthol and gallic acid were mixed at a molar ratio of 1:1 and stirred at 83°C to obtain a second mixture. Zinc oxide powder was mixed with the second mixture at a mass ratio of 1:5 and stirred at 77°C for 4 hours. After the reaction was completed, anhydrous ethanol was added and centrifuged to obtain a precipitate. The precipitate was washed three times with anhydrous ethanol and then dried to obtain the additive. The volume of anhydrous ethanol was twice the volume of the second mixture.

[0033] Preparation of Additive B: The additive and titanate coupling agent were mixed at a mass ratio of 1:0.3 and stirred at 70°C for 5 min. Then aluminum nitride powder was added and reacted for 1 h. After cooling, the mixture was centrifuged to obtain a precipitate. The precipitate was washed three times with anhydrous ethanol and then vacuum dried at 80°C to obtain Additive B.

[0034] The aluminum nitride powder has an average particle size of less than 100 nm, and the mass of aluminum nitride is 8% of the mass of the additive.

[0035] Among them, the mass content of praseodymium in the praseodymium-neodymium mixed rare earth metal is not less than 75%.

[0036] Preparation of raw materials: 30 parts praseodymium-neodymium mixed rare earth metals, 70 parts pure iron, 6 parts metallic cobalt, 1 part metallic niobium, 0.3 parts additive A and 1 part additive B.

[0037] Preparation of light rare earth Pr-based ultra-high magnetostrictive materials: Step 1: Place the praseodymium-neodymium mixed rare earth metals, pure iron, metallic cobalt, metallic niobium, additive A, and additive B into a vacuum induction melting furnace, and evacuate to 5.0 × 10⁻⁻⁻⁶. 2 The pressure is above Pa, and high-purity argon gas is introduced to -0.05 MPa. The mixture is then melted at 1500℃ to obtain a liquid alloy. The liquid alloy is then poured into a water-cooled copper mold to obtain an alloy ingot. Step 2: Vacuum homogenization annealing of the alloy ingot is carried out at a temperature of 1000℃ for 15 hours. After cooling, the alloy rod is obtained by wire cutting. Step 3: Place the alloy rod in a vacuum reactor and absorb hydrogen at room temperature. Then, dehydrogenate and crush it at 400°C to obtain the coarse material. The process parameters for dehydrogenation and crushing are set as follows: absorb hydrogen at room temperature to a pressure of 0.2 MPa, hold the pressure for 3 hours, then evacuate to below 1 Pa and heat to 350°C for dehydrogenation for 2 hours. Step 4: The rough material is oriented and pressed into shape under a magnetic field with a strength of 1T to obtain the intermediate product; Step 5: The intermediate product is encapsulated in a pyrophyllite pressure-transmitting medium, placed in a six-sided hydraulic press, and kept at 900℃ and 6GPa pressure for 30 minutes. After cooling to room temperature, a light rare earth Pr-based ultra-high magnetostrictive material is obtained.

[0038] Example 3: Preparation of reaction solution: Succinic acid and deionized water are mixed at a mass ratio of 5:95 and stirred until the succinic acid is completely dissolved to obtain an aqueous solution of succinic acid. Potassium dihydrogen phosphate is added to the aqueous solution of succinic acid and stirred at 200 rpm for 15 min to obtain the reaction solution. The mass of potassium dihydrogen phosphate is 3% of the mass of succinic acid.

[0039] Pretreatment of boron sludge: After drying the boron sludge, crush it to 80 mesh. Mix the crushed boron sludge with the reaction solution at a mass ratio of 1:5, add polyethylene glycol-400, stir at 300 rpm for 30 min, let stand for 10 h, filter, add 5% sodium bicarbonate aqueous solution to the filter residue, react for 10 min, filter, dry the filter residue, and crush it to 100 mesh to obtain the pretreated boron sludge, wherein the mass of sodium bicarbonate aqueous solution is 30% of the mass of the filter residue.

[0040] Preparation of Additive A: Anhydrous magnesium chloride powder and silicon powder were mixed at a mass ratio of 5:1 and placed in a ball mill jar. The mixture was ball-milled at 400 rpm for 4 hours to obtain a mixed powder. Pretreated boron mud was mixed with the mixed powder at a mass ratio of 1:2.5 and calcined at 800℃ for 4 hours under argon protection. After cooling, the mixture was pulverized and passed through a 300-mesh sieve. A 10% hydrochloric acid solution was added and reacted at 60℃ for 2 hours. After the reaction was completed, the mixture was filtered. The filter residue was washed with deionized water until neutral. The washed filter residue was vacuum dried at 100℃ to obtain Additive A. The mass of the hydrochloric acid was 7 times the mass of the mixed powder.

[0041] Preparation of the additive: Menthol and gallic acid were mixed at a molar ratio of 1:1 and stirred at 85°C to obtain a second mixture. Zinc oxide powder was mixed with the second mixture at a mass ratio of 1:6 and stirred at 80°C for 5 hours. After the reaction was completed, anhydrous ethanol was added and centrifuged to obtain a precipitate. The precipitate was washed three times with anhydrous ethanol and dried to obtain the additive. The volume of anhydrous ethanol was three times the volume of the second mixture.

[0042] Preparation of Additive B: The additive and titanate coupling agent were mixed at a mass ratio of 1:0.4 and stirred at 80°C for 7 min. Then aluminum nitride powder was added and reacted for 1 h. After cooling, the mixture was centrifuged to obtain a precipitate. The precipitate was washed three times with anhydrous ethanol and then vacuum dried at 90°C to obtain Additive B.

[0043] The aluminum nitride powder has an average particle size of less than 100 nm, and the mass of aluminum nitride is 10% of the mass of the additive.

[0044] Among them, the mass content of praseodymium in the praseodymium-neodymium mixed rare earth metal is not less than 75%.

[0045] Raw material preparation: 35 parts praseodymium-neodymium mixed rare earth metals, 75 parts pure iron, 8 parts metallic cobalt, 2 parts metallic niobium, 0.5 parts additive A and 2 parts additive B.

[0046] Preparation of light rare earth Pr-based ultra-high magnetostrictive materials: Step 1: Place the praseodymium-neodymium mixed rare earth metals, pure iron, metallic cobalt, metallic niobium, additive A, and additive B into a vacuum induction melting furnace, and evacuate to 5.0 × 10⁻⁻⁻⁶. 2 The pressure is above Pa, and high-purity argon gas is introduced to -0.05 MPa. The mixture is then melted at 1550 °C to obtain a liquid alloy. The liquid alloy is then poured into a water-cooled copper mold to obtain an alloy ingot. Step 2: Vacuum homogenization annealing is performed on the alloy ingot at a temperature of 1050℃ for 20 hours. After cooling, the alloy rod is obtained by wire cutting. Step 3: Place the alloy rod in a vacuum reactor and absorb hydrogen at room temperature. Then, dehydrogenate and crush it at 500°C to obtain the coarse material. The process parameters for dehydrogenation and crushing are set as follows: absorb hydrogen at room temperature to a pressure of 0.2 MPa, maintain the pressure for 4 hours, then evacuate to below 1 Pa and heat to 400°C for dehydrogenation for 3 hours. Step 4: The rough material is oriented and pressed into shape under a magnetic field with a strength of 2.5T to obtain the intermediate product; Step 5: The intermediate product is encapsulated in a pyrophyllite pressure-transmitting medium, placed in a six-sided hydraulic press, and kept at 1000℃ and 8GPa pressure for 60 minutes. After cooling to room temperature, a light rare earth Pr-based ultra-high magnetostrictive material is obtained.

[0047] Comparative Example 1: The difference between this comparative example and Example 1 is that this comparative example does not contain additive A.

[0048] Comparative Example 2 differs from Example 1 in that it does not contain additive B.

[0049] Comparative Example 3 differs from Example 1 in that hydrogen breakage is not performed during the preparation of the magnetostrictive material in this comparative example.

[0050] Comparative Example 4 differs from Example 1 in that the magnetostrictive material prepared in this comparative example does not undergo magnetic field orientation and hot-pressing synthesis processes.

[0051] Performance testing: The performance of the light rare earth Pr-based ultra-high magnetostrictive materials treated in Examples 1-3 and Comparative Examples 1-4 was tested, and the test data are recorded in the table below: Table 1 Test item Saturation magnetostrictive coefficient (λs / ppm) Bending strength (σbb / MPa) Curie temperature (Tc / °C) Example 1 1268 389 285 Example 2 1271 391 290 Example 3 1270 390 289 Comparative Example 1 780 251 255 Comparative Example 2 830 267 275 Comparative Example 3 970 305 280 Comparative Example 4 840 270 269 In the performance tests, the saturation magnetostriction coefficient was determined by strain gauge method (λs / ppm), the bending strength test was conducted in accordance with GB / T 232-2024, and the Curie temperature test was conducted in accordance with GB / T 43870.2-2024.

[0052] The data obtained from the performance tests show that the saturation magnetostriction coefficient, bending strength, and Curie temperature of the light rare earth Pr-based magnetostrictive materials prepared in Examples 1-3 are significantly higher than those in Comparative Examples 1-4. This indicates that additive A, through its selective enrichment and pinning effect at grain boundaries, effectively refines the alloy grains and suppresses grain coarsening at high temperatures, providing a uniform and stable microstructure basis for magnetic domain reversal. At the same time, additive B, by optimizing the interfacial bonding state between the rare earth phase and the ferromagnetic matrix, significantly reduces the movement resistance of the domain walls at the phase boundary and promotes the synergistic flipping of magnetic domains under an external magnetic field, thereby jointly improving the magnetostrictive response and mechanical integrity of the material. Through the dual regulation of grain boundaries and phase boundaries, the two additives solve the problems of insufficient magnetostrictive performance and brittle fracture caused by coarse grains and weak interfacial bonding in traditional praseodymium-iron-based alloys.

[0053] Furthermore, the complete hydrogen breakup and magnetic field orientation hot pressing process plays a crucial role in material densification and texture formation. Compared with the examples, Comparative Examples 3 and 4 lacked the hydrogen breakup and high-pressure orientation steps, resulting in structural defects and disordered magnetic domain orientation within the materials, manifested as deterioration in magnetostriction coefficient and bending strength. This indicates that the specific preparation process adopted in this invention is crucial for forming a highly oriented and dense Laves phase texture, and is an indispensable process guarantee for achieving ultra-high magnetostriction performance.

[0054] By comparing and analyzing the relevant data in the table, it can be seen that the light rare earth Pr-based ultra-high magnetostrictive material prepared by the present invention not only has a high magnetostriction coefficient, but also has excellent mechanical strength and thermal stability. This shows that the light rare earth Pr-based magnetostrictive material and its preparation method provided by the present invention achieve a good balance between performance and cost, have a broader market prospect, and are more suitable for promotion.

[0055] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0056] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A light rare earth Pr-based ultrahigh magnetostrictive material, characterized in that, The additive A is prepared by the following steps: mixing the anhydrous magnesium chloride powder and the silicon powder in a mass ratio of (3-5):1, placing them in a ball mill tank, ball milling at a speed of 300-400 rpm for 2-4 h to obtain a mixed powder, mixing the boron mud and the mixed powder in a mass ratio of 1:(1.5-2.5), calcining at 650-800 ℃ under argon protection for 2-4 h, cooling, crushing, passing through a 200-300 mesh sieve, adding a hydrochloric acid solution with a mass concentration of 5-10% and reacting at 40-60 ℃ for 1-2 h, after the reaction, filtering, washing the residue with deionized water until neutral, drying the washed residue at 80-100 ℃ under vacuum to obtain the additive A, wherein the mass of the hydrochloric acid is 5-7 times the mass of the mixed powder. The boron mud needs to be pretreated before preparing the additive A. The pretreatment of the boron mud includes the following steps: drying and crushing the boron mud to 60-80 mesh, mixing the crushed boron mud and a reaction solution in a mass ratio of 1:5, adding polyethylene glycol-400, stirring at 200-300 rpm for 20-30 min, standing for 8-10 h, filtering, adding a 5% sodium bicarbonate aqueous solution to the residue, reacting for 8-10 min, filtering, drying the residue, crushing it to 80-100 mesh to obtain the pretreated boron mud, wherein the mass of the sodium bicarbonate aqueous solution is 25-30% of the mass of the residue.

2. The light rare earth Pr-based ultrahigh magnetostrictive material according to claim 1, characterized in that, The reaction solution is prepared by the following method: mixing succinic acid and deionized water in a mass ratio of 5:(90-95), stirring until the succinic acid is completely dissolved to obtain a succinic acid aqueous solution, adding potassium dihydrogen phosphate to the succinic acid aqueous solution, stirring at a speed of 100-200 rpm for 10-15 min to obtain the reaction solution, wherein the mass of the potassium dihydrogen phosphate is 3% of the mass of the succinic acid.

3. The light rare earth Pr-based ultrahigh magnetostrictive material according to claim 2, characterized in that, The additive B is prepared by the following method: mixing the additive and the titanate coupling agent in a mass ratio of 1:(0.2-0.4), stirring and reacting at 60-80 ℃ for 3-7 min, then adding aluminum nitride powder, reacting for 0.5-1 h, cooling, centrifuging to obtain a precipitate, washing the precipitate with anhydrous ethanol for 2-3 times, and vacuum drying at 70-90 ℃ to obtain the additive B.

4. The light rare earth Pr-based ultrahigh magnetostrictive material according to claim 3, characterized in that, ​ 5. The light rare earth Pr-based ultrahigh magnetostrictive material according to claim 4, characterized in that, ​ 6. The light rare earth Pr-based ultrahigh magnetostrictive material of claim 1, characterized in that, ​ 7. The light rare earth Pr-based ultrahigh magnetostrictive material according to claim 6, characterized in that, The additive is prepared by the following method: mixing menthol and gallic acid at a molar ratio of 1:1, stirring at 80-85 DEG C to obtain a second mixture, mixing zinc oxide powder and the second mixture at a mass ratio of 1:(4-6), stirring and reacting at 75-80 DEG C for 3-5 h, after the reaction is completed, adding anhydrous ethanol, centrifugal separation treatment to obtain a precipitate, washing the precipitate with anhydrous ethanol for 2-3 times, and drying to obtain the additive, wherein the volume of anhydrous ethanol is 1-3 times the volume of the second mixture.

8. The light rare earth Pr-based ultrahigh magnetostrictive material according to claim 6, characterized in that, The average particle size of the aluminum nitride powder is less than 100 nm, and the mass of the aluminum nitride is 5-10% of the mass of the additive.

9. The light rare earth Pr-based ultrahigh magnetostrictive material of claim 1, characterized in that, The mass content of praseodymium in the praseodymium-neodymium mixed rare earth metal is not less than 75%.

10. The method of claim 1-9, wherein the method is characterized by: The method comprises the following steps: Step one: placing praseodymium-neodymium mixed rare earth metal, pure iron, metal cobalt, metal niobium, additive A and additive B into a vacuum induction melting furnace, vacuumizing to 5.0*10-2 Pa or above, filling high-purity argon to-0.05 MPa, melting at 1450-1550 DEG C to obtain an alloy liquid, pouring the alloy liquid into a water-cooled copper mold to obtain an alloy ingot; Step two: vacuum homogenizing annealing the alloy ingot, the annealing temperature is 1050 DEG C, the annealing time is 10-20 h, cooling, and obtaining an alloy rod by wire cutting; Step three: placing the alloy rod in a vacuum reactor, absorbing hydrogen at room temperature, and then performing dehydrogenation crushing treatment at 300-500 DEG C to obtain a crude material, wherein the process parameters of the dehydrogenation crushing treatment are set as follows: absorbing hydrogen at room temperature until the pressure is 0.1-0.2 MPa, maintaining the pressure for 2-4 h, vacuumizing to 1 Pa or below, and dehydrogenating by increasing the temperature to 300-400 DEG C, and the dehydrogenation time is 1-3 h; Step four: orienting and pressing the crude material under a magnetic field with a magnetic field intensity of 1.5-2.5 T to obtain an intermediate product; and step five: packaging the intermediate product in pyrophyllite pressure transmission medium, placing it in a six-surface hydraulic press, and performing heat treatment and pressure treatment at 800-1000 DEG C and a pressure of 4-8 GPa for 10-60 min, cooling to room temperature to obtain a light rare earth Pr-based ultrahigh magnetostrictive material.

Citation Information

Patent Citations

  • High-strength tenacity agglomeration neodymium-iron-boron magnet reconstructed by crystal boundary phase and preparation method thereof

    CN101325109A

  • Preparation method of high-performance sintered NdFeB magnet

    CN107464644A

  • Rare earth magnet and its manufacturing method

    JP2004327930A

  • Method of manufacturing anisotropic bond magnet, magnetic circuit, and anisotropic bond magnet

    JP2010199222A